Analisis Pengendalian Kualitas Pada Proses Coating di PT ABC dengan Pendekatan Statistical Quality Control (SQC) dan FMEA - Khoiri, Halwa Annisa; Aryani, Wilis Herlin (Jurnal Sains dan Aplikasi Keilmuan Teknik Industri (SAKTI), 2025)
PT ABC is a manufacturing company operating in the construction and fabrication sector. One of the projects currently undertaken by PT ABC is the manufacture of 12 sets of off-screen bars. In this process, the coating stage shows a high defect rate, accounting for 35.1% of total defects. This study aims to analyze the quality control process at the coating stage using Statistical Quality Control (SQC) and Failure Mode and Effects Analysis (FMEA). The SQC tools applied include control charts, Pareto diagrams, and fishbone diagrams. SQC is used to identify dominant defect types and their contributing factors, followed by FMEA to determine risk priorities using the Risk Priority Number (RPN) approach. The integration of these two methods provides a comprehensive framework for quality improvement. The results show that the two dominant defects are mottling and dust spray. Based on the RPN calculations, the highest RPN value is 280, caused by inconsistent spraying at corner areas leading to mottling defects. This is followed by excessive spraying distance in dust spray defects with an RPN of 252. Other significant causes are related to human factors, namely operators failing to clean the workpiece surface in dust spray defects and lack of operator attentiveness in mottling defects, both with an RPN value of 210. Based on these findings, several improvement recommendations are proposed, including operator retraining, standardization of spraying distance and angle, and the implementation of surface cleaning procedures prior to the coating process.